Companion orthogonal polynomials - Ranga, A. S. (Elsevier B.V., 1996)
We give some properties relating the recurrence relations of orthogonal polynomials associated with any two symmetric distributions d phi(1)(x) and d phi(2)(x) such that d phi(2)(x) = (I + kx(2))d phi(1)(x). AS applications of these properties, recurrence relations for many interesting systems of orthogonal polynomials are obtained.
Keywords: symmetric orthogonal polynomials; Three term recurrence relations; strong distributions